Synthetic cathinones and stereochemistry: S enantiomer of mephedrone reduces anxiety- and depressant-like effects in cocaine- or MDPV-abstinent rats. (1st September 2017) - Philogene-Khalid, Helene L.; Hicks, Callum; Reitz, Allen B.; Liu-Chen, Lee-Yuan; Rawls, Scott M.
Highlights: S -mephedrone effects against psychostimulant withdrawal were investigated. S -mephedrone reduced anxiety and depression during cocaine abstinence. S -mephedrone reduced anxiety and depression during MDPV abstinence. S -mephedrone displayed affinity, but not agonist activity, for 5-HT2 receptors (2A–2C). Abstract: Background and purpose: The neuropharmacological profile of the synthetic cathinone mephedrone (MEPH) is influenced by stereochemistry. Both MEPH enantiomers are monoamine transporter substrates, but R -MEPH is primarily responsible for rewarding effects of MEPH as it produces greater locomotor activation and intracranial self-stimulation than S -MEPH. S -MEPH is a 50-fold more potent 5-HT releaser than R -MEPH and does not place preference in rats. MEPH is also structurally similar to the cathinone derivative bupropion, an antidepressant and smoking cessation medication, suggesting MEPH has therapeutic and addictive properties. Methods: We tested the hypothesis that S -MEPH reduces anxiety- and depression- like behaviors in rats withdrawn from chronic cocaine or methylenedioxypyrovalerone (MDPV) using the elevated plus maze (EPM) and forced swim test (FST), respectively. Rats were tested 48-h after a binge-like paradigm (3×/day for 10 days in 1-h intervals) of cocaine (10 mg/kg), MDPV (1 mg/kg) or saline. In vitro studies assessed the receptor binding and activity of S -MEPH. Key results: Rats withdrawn from chronic cocaine or MDPV displayed an increase in anxiety- and depression-like behaviors that was antagonized by treatment with S -MEPH (10, 30 mg/kg). S -MEPH displayed affinity, but not agonist activity, for 5-HT2 receptors (2A–2C) and showed negligible affinity for dopaminergic, adrenergic and nicotinic receptors. Conclusion and implication: S -MEPH attenuated withdrawal behaviors following chronic cocaine or MDPV, perhaps through 5-HT release and/or 5-HT2 receptor interactions. The present data suggest S -MEPH may be a possible structural and pharmacological template to develop maintenance therapy for acute anxiety and depression during early withdrawal from psychostimulant abuse.